2020
DOI: 10.1155/2020/8869401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbial Transglutaminase on Technological, Rheological, and Microstructural Indicators of Minced Meat with the Addition of Plant Raw Materials

Abstract: The aim of the study was to analyse the effects of transglutaminase on the physicochemical, technological, rheological, and microstructural indicators of minced meat with the addition of plant raw materials. The formulations of minced meat from beef trimming, hemp protein, and flax flour were optimized in terms of biological value and optimal content of essential amino acids. The addition of plant components in amounts greater than 18% caused an increase in the content of protein, fat, and ash in the minced sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Our study showed that a fat substitute with flaxseed flour (G, GT, GE, and GET) improved the WHC about 54-60% as compared with those of the control samples, depending on the storage period and variant. A similar trend was observed by Zinina et al [38], who observed an increased WHC parameter when flaxseed flour was used. In contrast, a study by Sharefiabadi et al [39] revealed that the addition of flaxseed flour and coconut flour did not improve the WHC parameter in chicken pasties.…”
Section: Whc Analysis Weight Loss and Cooking Loss Analysissupporting
confidence: 88%
“…Our study showed that a fat substitute with flaxseed flour (G, GT, GE, and GET) improved the WHC about 54-60% as compared with those of the control samples, depending on the storage period and variant. A similar trend was observed by Zinina et al [38], who observed an increased WHC parameter when flaxseed flour was used. In contrast, a study by Sharefiabadi et al [39] revealed that the addition of flaxseed flour and coconut flour did not improve the WHC parameter in chicken pasties.…”
Section: Whc Analysis Weight Loss and Cooking Loss Analysissupporting
confidence: 88%
“…In our study, it was shown that enrichment of the meat product with hemp products had a beneficial effect on increasing the protein content ( p < 0.05) in group P 1 , with a higher content of hemp seeds compared to group P 2 and the control group ( Table 3 ). Similar results have also been shown by other authors: Zając et al [ 20 ], Bozhko et al [ 38 ], Augustyńska-Prejsnar et al [ 32 ], and Zinina et al [ 18 ], who used high-protein hemp products (hulled hemp seeds, hemp flour, and hemp protein) to enrich meat products. In contrast, Kerner et al [ 5 ] did not observe an increase in protein in a pork burger after the introduction of 2% hemp cake.…”
Section: Resultssupporting
confidence: 87%
“…In studies by Sun et al [ 39 ], adding hydrated hemp flour to poultry sausage significantly reduced the protein and fat content, but increased the total ash and fiber content. Vegetable proteins are relatively low in essential amino acids compared to proteins of animal origin [ 18 ]. In our research, the introduction of hemp components into the recipe composition did not significantly change the amino acid profile of the final products ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vermicomposting ensures the production of biohumus with high moisture capacity, flowability, which has associations of microorganisms useful for plants and soil ( Titova, 2004 ). The main factor in the violation of the integrity and structure of natural communities, changes in the properties of the natural environment is human activity ( Zinina et al, 2010 ; Zainutdinov et al, 2011 ; Zinina et al, 2013 ). The growth in the amount of waste gives rise to the need to search for new and optimized known methods for the neutralization and disposal of substances harmful to nature and humans.…”
Section: Introductionmentioning
confidence: 99%